Relationship between the Use of Management Information Systems and Employee Job Performance: Evidence from Kenindia Assurance Company Limited - Phyllis Osodo, Owino; Jemaiyo, Beatrice (British Journal of Marketing Studies, 2015)
Organizations are continually changing their information systems in order to keep up with the ever-changing business environment and, more importantly, to stay competitive. These changes do affect employee performance, either positively or negatively. Management information systems (MIS) should facilitate planning, especially in large organizations where managers often do not have a good personal touch with the scene of operations. In this regard, therefore, a good management information system helps to decentralize authority to enable effective management of organizational processes to be undertaken making control easier. MIS should facilitate coordination by integrating specialized activities and keeping each department or function of the organization aware of the problems of the other departments. Based on a study of Kenindia Assurance Company in Kenya, this paper examines the influence of management information as a strategic tool of management on employee performance. The respondents of the study were the branch managers, underwriting officers, claims and legal managers, information technology managers and operations managers. The study adopted a qualitative research design. Data was collected through interviews and questionnaires. Inferential statistics and parametic methods, like the Likert and Ordinal scale, were used to analyse data. The study findings revealed that the use of MIS had enhanced access to resources and employee satisfaction. The results of the study indicate that the new IS tends to cause fear and anxiety among employees who think that the system is out to take their jobs. This is also attributed to confusion of responsibilities and duties of IS among employees. In addition, some of the senior officials in management feel that information systems usurp their power and authority. However, from the study findings, it is clear that employees generally improve their performance whenever IS are used. Based on the results of the case study at Kenindia Assurance Ltd., it is recommended that MIS should be used as a strategic tool to improve employee performance. Managers must have appropriate managerial skills in order to stipulate their core functions of management such as coordinating, directing, controlling, organizing and planning. Moreover, the increase in financial gains owing to improved employee performance should be a motivator to some managers to relinquish their fears that IS are meant to usurp their official powers rather than enhance organizational performance.